2002
DOI: 10.1381/096089202762552395
|View full text |Cite
|
Sign up to set email alerts
|

Gallbladder Management in Obesity Surgery

Abstract: Prophylactic cholecystectomy is left to the discretion of the surgeon when RYGBP is used. There has been an increase in cholecystectomy and malabsorptive operations during the last 15 years. When most of the small bowel is bypassed, all remaining gallbladders are removed. For patients with simple restriction operations, normal-appearing gallbladders are usually left in place. Urso-deoxycholic acid during rapid weight loss for prevention of gallstone formation is used in one-third of patients with remaining gal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
0
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(44 citation statements)
references
References 6 publications
2
40
0
2
Order By: Relevance
“…Two hundred of 796 (25.1%) patients had evidence of previous gallbladder diseases as evidenced by either history of cholecystectomy or cholelithiasis detected on routine preoperative transabdominal ultrasound. This finding was similar to those observed in other studies [17][18][19]. Additionally, 65 of 796 (8.2%) of patients were found to have asymptomatic gallstones or sludge on routine preoperative ultrasound and were recommended to undergo concomitant cholecystectomy as is routine at our institute.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Two hundred of 796 (25.1%) patients had evidence of previous gallbladder diseases as evidenced by either history of cholecystectomy or cholelithiasis detected on routine preoperative transabdominal ultrasound. This finding was similar to those observed in other studies [17][18][19]. Additionally, 65 of 796 (8.2%) of patients were found to have asymptomatic gallstones or sludge on routine preoperative ultrasound and were recommended to undergo concomitant cholecystectomy as is routine at our institute.…”
Section: Discussionsupporting
confidence: 91%
“…It has been postulated that, during rapid weight loss, cholesterol was mobilized from tissues stores and was excreted in bile, resulting in so-called lithogenic bile due to increased bile cholesterol saturation index. Others found that increased gallbladder secretion of mucin and calcium and increased presence of prostaglandins and arachidonic acid in bile had significant attribution to gallstone formation [10][11][12][13]. The risks of developing gallstones between the different weight reduction procedures, such as a complex restrictive-malabsorptive procedure or simple restrictive procedure, may be different.…”
Section: Discussionmentioning
confidence: 99%
“…It has been postulated that, during rapid weight loss, cholesterol was mobilized from tissues stores and was excreted in bile, resulting in socalled lithogenic bile due to increased bile cholesterol saturation index. Others found that increased gallbladder secretion of mucin and calcium and increased presence of prostaglandins and arachidonic acid in bile had significant attribution to gallstone formation [5,9,28,29]. Of the 19 cases developed gallstones in our study, 8 (42%) were symptomatic.…”
Section: Open Access Ssmentioning
confidence: 46%
“…In addition to increased frequency of various other diseases, obese patients have increased frequency of gallstones compared to the normal population (21-33%). The increase in the secretion of cholesterol by the liver and the reduced contractility of the gallbladder due to the increased cholesterol concentration without a proportional increase in phospholipids and bile salts play an important role in the formation of gallstones (12)(13)(14).…”
Section: Discussionmentioning
confidence: 99%